Pestalotiopsis desseminata PADA JAMBU MENTE BIOLOGI DAN INTERAKSINYA DENGAN Helopeltis antonii - ESTHER M. ADHI; SUPRIADI SUPRIADI; S. RAHAYUNINGSIH; D. KILIN; NURI KARYANI (Jurnal Penelitian Tanaman Industri, 2000)
Pestalotiopsis desseminata on cashew: its biology and interaction with Helopeltis antoniiPestalotiopsis desseminata is one of pathogens causing leaf spots. die-back of shoots and inflorescence of cashew plant. It is assumed there is an interaction between the attack of Helopeltis antonii and the fungus in Ihe ield so that the damage becomes more devastating. The objectives of (his research were to investigate several aspects of fungal biology (pathogenicity, mycelial growth, acervuli production, sensitivity to fungicides) and its interaction with //. antonii. The esearch was carried out from April 1999 to March 2000 at the laboratory and green house of Pest and Disease Department Research Institute for Spice and Medicinal Crops, Bogor. /' desseminata was diectly isolated from cashew leaves. Pathogenicity test of P. desseminata isolate was conducted on cashew seedlings. The fungal growth and fungicide effects were carried out in vitro on agar medium. The interaction between P. desseminata and H. antonii was examined by inoculating the fungus and insect, either individually or in combination, on cashew seedlings. The results showed that P. desseminata isolate fomis black spherical acervuli containing oblongs conidia with 5 cells, and the outermost cell has 3 flagellate. Acervuli could only be produced on the cultue illuminated continuously by 600 lux translucent lamp. Pathogenicity test of several isolates of /' desseminata on cashew seedlings caused spherical leaf spot symptom, individually or coalesced as bigger leaf spots. In vitro fungal mycelia growth could be suppressed by several fungicides, including bcnomyl 50% (I ppm) and Uiiopanate-mcthyl 70% (10 ppm) Combining inoculation between P. desseminata and //. antonii resulted in moe severe (devastating) die-back compared with individually inoculated.